Review of the Chinese species of the genus Scelimena Serville, 1838 (Tetrigidae: Scelimeninae: Scelimenini) - Lao, Chuangyu; Kasalo, Niko; Gao, Fan; Deng, Weian; Skejo, Josip (Zootaxa, 2022)
A brief preliminary revision of the genus Scelimena Serville, 1838 (Tetrigidae: Scelimeninae: Scelimenini) from PR China is presented. Scelimena pyrroma Lao, Kasalo, Gao, Deng et Skejo sp. nov. is described from Hainan, Ding'an, based on a female holotype and a male paratype, and an additional photograph of a female in the natural habitat from Wuzhi National Nature Reserve (Wuzhi-shan Mountain). Specimens of this new species were hitherto reported from Hainan as S. dentiumeris (Hancock, 1907), a species endemic to Borneo. The new species is easily distinguished from its congeners by the presence of prominent yellow humeral tubercles and by the lateral pronotal spines directed forwards. The new species from Hainan and S. chinensis (Hancock, 1915) from Vietnam are assigned to Scelimena producta species group based on the similarity with S. producta (Serville, 1838), which is characterized by the humeral angles with tubercles, wide vertex, and toothed ventral margins of hind femora, while S. boettcheri Günther, 1938 from Palawan is assigned to Scelimena discalis species group, based on the tuberculated median carina. Scelimena dammermanni Günther, 1938, stat. nov., hitherto regarded as a subspecies of S. producta, is elevated to a species level because it lacks ventral spines on the hind legs, present in all S. producta individuals. New synonymy is established: Scelimena melli Günther, 1938, =Scelimena brevispina Cao et Zheng, 2011, syn. nov.; =Scelimena wulingshana Zheng, 1993, syn. nov.; =Eufalconoides guizhouensis Zheng et Shi, 2006, syn. nov. Scelimena melli, S. guangxiensis Zheng et Jiang, 1994 from southern China and S. kempi (Hancock, 1915) from NE India are assigned to S. bellula species group on the basis of similarity to S. bellula Storozhenko et Dawwrueng, 2015. Further research should determine whether S. spicupennis Zheng & Ou, 2003 represents a valid species or a synonym of another Scelimena species, as well as if S. nitidogranulosa Günther, 1938 and S. guangxiensis Zheng & Jiang, 1994 represent separate species or whether they are conspecific. Specimens of S. nitidogranulosa from Hainan reported by Liang & Zheng in 1998 are in fact Platygavialidium sinicum Günther, 1939. Scelimena songkrana Zha et Wen, 2017 is recorded from China for the first time. A key to Scelimena species found in PR China is also provided.